Study of Antibacterial and Anticancer Properties of bioAgNPs Synthesized Using Streptomyces sp. PBD-311B and the Application of bioAgNP-CNC/Alg as an Antibacterial Hydrogel Film against P. aeruginosa USM-AR2 and MRSA - Hemalatha Murugaiah; Chow Lun Teh; Kai Chew Loh; Ahmad Ramli Mohamad Yahya; Nur Asshifa Md Noh; Noor Hana Hanif Abu Bakar; Daruliza Kernain; Rokiah Hashim; Yazmin Bustami (Molecules, 2021)
Here, we report the extracellular biosynthesis of silver nanoparticles (AgNPs) and determination of their antibacterial and anticancer properties. We also explore the efficacy of bioAgNPs incorporated in cellulose nanocrystals (CNCs) and alginate (Alg) for the formation of an antibacterial hydrogel film. Streptomyces sp. PBD-311B was used for the biosynthesis of AgNPs. The synthesized bioAgNPs were characterized using UV-Vis spectroscopy, TEM, XRD, and FTIR analysis. Then, the bioAgNPs’ antibacterial and anticancer properties were determined using TEMA and cytotoxicity analysis. To form the antibacterial hydrogel film, bioAgNPs were mixed with a CNC and Alg solution and further characterized using FTIR analysis and a disc diffusion test. The average size of the synthesized bioAgNPs is around 69 ± 2 nm with a spherical shape. XRD analysis confirmed the formation of silver nanocrystals. FTIR analysis showed the presence of protein capping at the bioAgNP surface and could be attributed to the extracellular protein binding to bioAgNPs. The MIC value of bioAgNPs against P. aeruginosa USM-AR2 and MRSA was 6.25 mg/mL and 3.13 mg/mL, respectively. In addition, the bioAgNPs displayed cytotoxicity effects against cancer cells (DBTRG-0.5MG and MCF-7) and showed minimal effects against normal cells (SVG-p12 and MCF-10A), conferring selective toxicity. Interestingly, the bioAgNPs still exhibited inhibition activity when incorporated into CNC/Alg, which implies that the hydrogel film has antibacterial properties. It was also found that bioAgNP-CNC/Alg displayed a minimal or slow release of bioAgNPs owing to the intermolecular interaction and the hydrogel’s properties. Overall, bioAgNP-CNC/Alg is a promising antibacterial hydrogel film that showed inhibition against the pathogenic bacteria P. aeruginosa and MRSA and its application can be further evaluated for the inhibition of cancer cells. It showed benefits for surgical resection of a tumor to avoid post-operative wound infection and tumor recurrence at the surgical site.